Pengaruh harga dan kualitas produk terhadap keputusan pembelian produk snack french fries pt. siantar top di nusa dua - Dessy Widyanasari; Dian Derisyani (STIMI Handayani Denpasar, 2023)
This study aims to analyze and want to know the magnitude of the influence of price and product quality on purchasing decisions for French Fries products, besides that it also wants to know the price comparison of other products, namely Bee Kris snack. This type of research uses a quantitative approach. The method of data collection in this study uses a questionnaire. The measurement scale used in this study is the Likert scale. The analytical technique used is descriptive statistical analysis and normality analysis technique consisting of f test and t test. The data in this study were processed using For Windows SPSS 21